Radiographic evaluation of the cardiac silhouette in clinically normal Poodles through the vertebral heat size (VHS) method - Pinto, Ana Carolina B. C. Fonseca; Iwasaki, Masao (Brazilian Journal of Veterinary Research and Animal Science, 2004)
Many measurement methods have been proposed in order to minimize the subjectivity of the empire radiographic evaluation of the cardiac silhouette. This study intended to establish the VHS (vertebral heart size) value in Poodle dogs, which are a widely spread breed, applying the Buchanan e Bucheler¹ measurement method. Thirty healthy dogs, males and females, 1 to 6 years old were selected and undergone to right lateral and ventrodorsal thoracic radiographs that were first empirically evaluated. Then, Buchanan e Bucheler¹ method was applied to the cardiac silhouette and thoracic depth and width. Empiric evaluation did not show any important radiographic changes in twenty one dogs (70%). VHS measurements noticed to be smaller or equal as 10.5 vertebrae in 80% of dogs. The range of minimum (9.2 vertebrae) and maximum (11.1 vertebrae) VHS values had normal distribution with a 10.12 media and 0,51 standard deviation. Normal distribution was also noticed in depth/width ratio, with a 0,84 media and a 0.09 standard deviation with minimum and maximum values of 0.64 and 1.04 respectively. 40% of dogs showed VHS values greater than the 10.12 vertebrae found in this study, it suggests that this value should be used as upper limit for Poodle dogs. The upper limit should be 11 vertebrae as 96.67% of the dogs of this study presented VHS smaller than it. Based on the results, we suggest that a 10,5 to 11 vertebrae interval should be considered the upper limit value to Poodles with 0,84 + 0,09 depth/width ratio as once only one dog showed a measure that exceeded 11 vertebrae.